Pelaksanaan Pembelajaran Daring Materi PJOK Di SMA Negeri Se-Kecamatan Brebes Tahun 2021 - Nur Hilal Al Faritsi; Tri Nurharsono (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to find out the appropriate implementation for physical education subjects at State Senior High Schools throughout the Brebes District during the Covid-19 pandemic. This study uses a qualitative approach with a descriptive design. The results of research related to teacher learning planning make learning tools consisting of syllabus, lesson plans, teaching materials, assessment instruments and lesson schedules. Teachers carry out online learning with curriculum references that have been integrated according to current conditions. Compacted time allocation. Learning evaluation is carried out with student activity, PAS and PTS as well as making videos. The factors that influence online learning are digital literacy, student motivation and internet networks. The conclusion from the implementation of online learning of PE material in SMA Se-District Brebes, namely: the planning has been going well because the teacher has made and prepared all the learning tools. The implementation has been running properly because the strategy used by the teacher has been running well and effectively. The assessment/evaluation is in the good category because the assessment still contains 3 aspects, namely: affective, cognitive, and psychomotor. For the influencing factors can be minimized and reduced